Removal of aqueous natural organic pollutants using mixed mining solid wastes: coal fly ash and iron sludge - Sebata, Edith; Nyamunda, Benias C.; Zinyama, Ngceboyakwethu P.; Guyo, Upenyu; Moyo, Mambo (International Journals of Scientific Research Publications, 2016)
A new coagulant (ash sludge) has been developed from a mixture of mining solid wastes (coal fly ash and iron sludge). The chemical composition of the coal fly ash and iron sludge was characterised by X-ray fluorescence (XRF). The effectiveness of the coagulant was tested on the removal of aqueous natural organic matter and its improvement on total hardness, conductivity and turbidity of water under different pH and adsorbent dosages. The coagulant contains a high composition of Al3+ and Fe3+ ions. Ash sludge uses a lower optimum dosage (40 mgL-1) compared to the conventional coagulant, alum (55 mgL-1). At optimum pH 8, ash sludge removed 80.2% of the aqueous natural organic matter while alum removed 70.9%. Under optimised pH and coagulant dosage, alum coagulated water showed a higher total hardness (166 mgL-1) compared to ash sludge (155 mgL-1). Compared to alum, ash sludge exhibits an excellent potential in the removal of organic materials and gives water with better qualities.